Internationalization Trends in French Higher Education: An Historical Overview - Tronchet, Guillaume (International Higher Education, 2015)
For many policy makers in France, internationalization of higher education is a new subject. But people have short memories. They have forgotten—or simply do not know—that French universities were pioneers and leaders in internationalization between the end of the 19th and the middle of the 20th century, before being outshone by the United States and some other countries in Europe. Faced with today’s challenges of globalization, it is time for French universities to reclaim their own history.